Methods to investigate renal function - Velásquez, Manuel A. (1918)
As the urine by the organic liquid that most of the products of metabolism are eliminated, as well as drugs, once they have determined their action on the disturbed, just physiologism is able to assess the functional value of the kidney by qualitative and quantitative variations offered by the product of its operation.